Differential Effect of Two Mental Stress Tasks on Arterial Stiffness. (23rd October 2018) - Matsumura, Kenta; Noguchi, Hiroko; Rolfe, Peter; Yamakoshi, Takehiro; Matsuoka, Yutaka
Abstract: Acute mental stress is believed to induce transient arterial dysfunction, but relatively few data are available. We therefore examined the effect of mental stress tasks that could induce differential hemodynamic responses on arterial dysfunction. Forty‐eight participants conducted either a mental arithmetic (MA) task or a mirror‐tracing (MT) task. Cardiovascular indices and arterial stiffness were measured before, during, and after these tasks. Analysis revealed that increases in arterial stiffness during the task and during recovery were more pronounced for the MA than for the MT, and that evoked hemodynamic response was more myocardial for MA than for MT. These results clearly show that MA and MT tasks that induce differential hemodynamic responses have a differential effect on arterial stiffness. This finding sheds light on the underlying mechanism that may account for the relationship between cardiovascular reactivity and cardiovascular disease.